SOSIALISASI POLITIK DAN KOMUNIKASI POLITIK ANGGOTA DEWAN DALAM MEMBERIKAN PENDIDIKAN POLITIK DAN MENJARING ASPIRASI MASYARAKAT (Studi pada DPRD Kota Bandar Lampung dari Partai Demokrat Masa Bakti 2009-2014) - Bangun Suharti (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2014)
Bandar Lampung member parliament in political socialization and political communication needs to be audited. This is to determine the extent to which members of the parliament provide political education and the community in, especially constituents. Is the board members have been doing public aspirations and provide effective political education? Is the board members have been fighting for people's aspirations, and adapt them to the government program, that is pro-poor, pro-growth, pro-jobs and pro-environment?. This study was conducted by interviewing do persons, namely Bandar Lampung city councils of the Democratic Party of the tenure 2009-2014. Both speakers are selected, with the consideration that the Democratic Party is the party of government, so it is likely to be consistently fought for government programs. The party supports the government is assumed to provide a briefing to its cadres on these government programs. The results of this study indicate that, although the Democratic Party is the party of government, not necessarily consistently championed the concept of the development of pro-poor, pro-growth, pro-jobs and pro environment. The development concept is not disseminated to the public, especially the constituency. Background, the political interests of the ruling constraints, funding, scale ruler priorities in perspective, it is often an obstacle to implement the aspirations of the people.